Who is the critical thinker in higher education? A feminist re-thinking. Issue 5 (4th July 2018) - Danvers, Emily
ABSTRACT: Higher education's policy demands and pedagogical practices often take as their 'desirable' subject an unspecified body, failing to interrogate who the student is (and is not) in relation to differentiated access to power, privilege, and opportunity structures. This paper offers a feminist critique of such decontextualised theorisations of students and their critical thinking. Observation, focus group and interview data were collected with undergraduate social-science students at a UK university. This data revealed how students experience critical thinking as embodied, contingent and specifically gendered – with 90% of students naming a male when asked to describe a critical thinker. Consequently, this paper argues that who occupies a desirable position as a student critical thinker is not neutral or given, but intersects with students' embodied characteristics and the (increasingly divisive) socio-political context in which criticality is performed. Access to this key intellectual premium is therefore differentiated, raising questions around epistemic inclusion.